Movement efficiency in taekwondo side kick (Yop Chagi): a kinematic comparison between novice and experienced practitioners - Hidayat, Rahmat; Jin, Xianzhi; Dou, Chengji; Yang, Benyao (Frontiers in Physiology, 2026)
BackgroundThis study aimed to kinematically compare the Yop Chagi execution between novice and experienced university Taekwondo practitioners, focusing on movement efficiency.MethodsForty university students were allocated into two groups: Novice (n = 20; ≤6 months experience) and Experienced (n = 20; ≥3 years of competitive experience). Participants performed maximal effort side kicks targeting a pad at trochanter height. Movement was captured using two high-speed cameras (120 Hz). Kinematic variables included hip and knee joint angles at peak flexion/extension, peak angular velocities, linear velocity of the foot, and total kick execution time. Between-group differences were analysed using independent t-tests or Mann-Whitney U tests, with effect sizes (Cohen’s d) reported.ResultsThe experienced group demonstrated significantly larger hip abduction and knee flexion angles during the chamber phase (p < 0.01, d > 0.8), and greater knee extension at the point of impact (p < 0.01, d = 1.2) compared to novices. The experienced group also exhibited superior performance in peak hip and knee angular velocities (p < 0.01, d > 1.5), resulting in a 28% higher peak linear velocity of the foot (p < 0.001, d = 2.1). Furthermore, the total execution time was significantly shorter for the experienced group (p < 0.01, d = 1.4).ConclusionExperienced practitioners execute the Yop Chagi with a more efficient kinematic pattern, characterized by a larger range of motion, faster segmental velocities, and reduced execution time. These findings suggest that long-term training optimizes the proximal-to-distal kinematic sequence, enhancing kick performance.